Nanostructure, optical, electronic, photoluminescence and magnetic properties of Co-doped ZrO2 solgel films - Baqiah H.; Mustafa Awang Kechik M.; Pasupuleti J.; Zhang N.; Mohammed Al-Hada N.; Fat Chau C.; Li Q.; Xu S. (Elsevier B.V., 2024)
ZrO2 is a fascinating metal oxide with rich physical phenomenon and promised applications. In this study, the effects of chemical doping with Co+2 ions on nanostructure, electronic, optical, photoluminescence (PL), and magnetic properties of Zr1-xCoxO2 thin films (x = 0.0, 0.05, 0.1, and 0.15) prepared by solgel spin-coating method were investigated. The films exhibited a tetragonal structure with crystallinity improved with Co doping. Pure ZrO2 film showed a smooth surface morphology consisting of small particle size of 22 nm. The Co-doped ZrO2 films exhibited well-ordered holes, and their size and number increased with Co doping up to x = 0.1 and then decreased at x = 0.15. Root-mean-square roughness increased from 1.1 nm for pure ZrO2 to 16.5 nm for film x = 0.15. The Co ions in the films existed in a 2 + valence state. Energy band gap decreased with Co doping and had values of 4.40, 4.396, 4.392, and 4.170 eV for the films with x = 0.0, 0.05, 0.1, and 0.15, respectively. The PL spectra of films x = 0.00 and 0.05 are mainly comprised of two emission peaks